“LINGUISTIC AND NON-LINGUISTIC SCIENCES. UNIVERSAL FEATURES OF THE METHOD OF COMPARISON.” - ABDURAXMANOVA ZILOLA YOQUBJON QIZI; Dustmurodov Islom Jomurod o’g’li (Ta'lim innovatsiyasi va integratsiyasi, 2023)
Annotation: This article explores the method of comparison as a versatile tool applied across linguistic and non-linguistic sciences. It delves into its significance in fields such as historical linguistics, typological linguistics, anthropology, sociology, biology, and geology. The article highlights the universal features of this method, including data collection, hypothesis formation, cross-referencing, and pattern identification. It emphasizes the role of comparison in unraveling the complexities of languages, cultures, and the natural world, making it an invaluable approach for researchers across diverse disciplines.